INHIBITION OF CARSINOGENESIS BY SEED AND SOYBEAN MEAL EXTRACT IN COLON OF MICE: APOPTOSIS AND DYSPLASIA - Amalia, Anindini Winda; KUSMARDI; Elya, Berna; ARSIANTI, ADE (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Colon cancer is a major public health problem. Soybean has demonstrated chemopreventive and anticancer. Here, we have investigated the effect of a standardized seed and soybean meal extract (SE) with content of lunasin, here named grobogan extract (GE) and SE. They are botanical drug substance in experimental models of colon cancer in vivo. Methods: The effect of GE and SE was examined on the preneoplastic lesions (aberrant crypt foci), polyps and tumors induced by the carcinogenic agent azoxymethane (10 mg/kg) and dextran sodium sulfate 2% as well as in a xenograft model of colon cancer in mice. Results: GE and SE increased apoptosis (p=0.001). GE (150 mg/kg) has the highest impact level of apoptosis (p=0.009). GE and SE decreased dysplasia (p=0.024). GE (200 mg/kg) has the highest impact level of dysplasia (p=0.002), and SE (200 mg/kg) has the second impact level of dysplasia (p=0.003). Conclusions: GE and SE inhibition of colon carcinogenesis with increased level of apoptosis and decrease level of dysplasia. Keywords:Soybean, Lunasin, Colon cancer, Azoxymethane, Dextran sodium sulfate, Apoptosis, Dysplasia.